Scroll:Algebra >> subtract >> ps (4189)


Written Instructions:

For each Multiple Choice Question (MCQ), four options are given. One of them is the correct answer. Make your choice (1,2,3 or 4). Write your answers in the brackets provided..

For each Short Answer Question(SAQ) and Long Answer Question(LAQ), write your answers in the blanks provided.

Leave your answers in the simplest form or correct to two decimal places.



 

1)  

 (15f - 7c) from (-9f + 12c)

- ___c


Answer:_______________




2)  

 (29p - 3j) from (-7p + 25j)

- p

j


Answer:_______________




3)  

 (16x - 8e) from (-2x + 26e)

- x

e


Answer:_______________




4)  

 (13v - 8o) from (-9v + 16o)

- v

o


Answer:_______________




5)  

 (23y - 8k) from (-6y + 28k)

- y

k


Answer:_______________




6)  

 (17i - 8z) from (-5i + 21z)

- i

z


Answer:_______________




7)  

 (16q - 4u) from (-2q + 13u)

- q

u


Answer:_______________




8)  

 (19f - 2y) from (-7f + 18y)

- f

y


Answer:_______________




9)  

 (23m - 9x) from (-4m + 14x)

- ___m

x


Answer:_______________




10)  

 (28w - 6i) from (-7w + 16i)

- w

i


Answer:_______________




 

1)  

 (15f - 7h) from (-9f + 12h)

- Answer: 24f

Answer: 19h


SOLUTION 1 :

   (-9f + 12h) - (15f - 7h)

   =   - 9f + 12h - 15f + 7h

   =   (- 9f - 15f) +  (12h + 7h)

   =  (- 9 - 15)f + (12 + 7)h 

   = (- 24)f + (19)h

    = - 24f + 19h

 



2)  

 (29g - 3c) from (-7g + 25c)

- Answer: 36g

Answer: 28c


SOLUTION 1 :

   (-7g + 25c) - (29g - 3c)

   =   - 7g + 25c - 29g + 3c

   =   (- 7g - 29g) +  (25c + 3c)

   =  (- 7 - 29)g + (25 + 3)c 

   = (- 36)g + (28)c

    = - 36g + 28c

 



3)  

 (16j - 8m) from (-2j + 26m)

- Answer: 18j

Answer: 34m


SOLUTION 1 :

   (-2j + 26m) - (16j - 8m)

   =   - 2j + 26m - 16j + 8m

   =   (- 2j - 16j) +  (26m + 8m)

   =  (- 2 - 16)j + (26 + 8)m 

   = (- 18)j + (34)m

    = - 18j + 34m

 



4)  

 (13y - 8o) from (-9y + 16o)

- Answer: 22y

Answer: 24o


SOLUTION 1 :

   (-9y + 16o) - (13y - 8o)

   =   - 9y + 16o - 13y + 8o

   =   (- 9y - 13y) +  (16o + 8o)

   =  (- 9 - 13)y + (16 + 8)o 

   = (- 22)y + (24)o

    = - 22y + 24o

 



5)  

 (23s - 8k) from (-6s + 28k)

- Answer: 29s

Answer: 36k


SOLUTION 1 :

   (-6s + 28k) - (23s - 8k)

   =   - 6s + 28k - 23s + 8k

   =   (- 6s - 23s) +  (28k + 8k)

   =  (- 6 - 23)s + (28 + 8)k 

   = (- 29)s + (36)k

    = - 29s + 36k

 



6)  

 (17p - 8j) from (-5p + 21j)

- Answer: 22p

Answer: 29j


SOLUTION 1 :

   (-5p + 21j) - (17p - 8j)

   =   - 5p + 21j - 17p + 8j

   =   (- 5p - 17p) +  (21j + 8j)

   =  (- 5 - 17)p + (21 + 8)j 

   = (- 22)p + (29)j

    = - 22p + 29j

 



7)  

 (16l - 4e) from (-2l + 13e)

- Answer: 18l

Answer: 17e


SOLUTION 1 :

   (-2l + 13e) - (16l - 4e)

   =   - 2l + 13e - 16l + 4e

   =   (- 2l - 16l) +  (13e + 4e)

   =  (- 2 - 16)l + (13 + 4)e 

   = (- 18)l + (17)e

    = - 18l + 17e

 



8)  

 (19p - 2r) from (-7p + 18r)

- Answer: 26p

Answer: 20r


SOLUTION 1 :

   (-7p + 18r) - (19p - 2r)

   =   - 7p + 18r - 19p + 2r

   =   (- 7p - 19p) +  (18r + 2r)

   =  (- 7 - 19)p + (18 + 2)r 

   = (- 26)p + (20)r

    = - 26p + 20r

 



9)  

 (23g - 9t) from (-4g + 14t)

- Answer: 27g

Answer: 23t


SOLUTION 1 :

   (-4g + 14t) - (23g - 9t)

   =   - 4g + 14t - 23g + 9t

   =   (- 4g - 23g) +  (14t + 9t)

   =  (- 4 - 23)g + (14 + 9)t 

   = (- 27)g + (23)t

    = - 27g + 23t

 



10)  

 (28v - 6f) from (-7v + 16f)

- Answer: 35v

Answer: 22f


SOLUTION 1 :

   (-7v + 16f) - (28v - 6f)

   =   - 7v + 16f - 28v + 6f

   =   (- 7v - 28v) +  (16f + 6f)

   =  (- 7 - 28)v + (16 + 6)f 

   = (- 35)v + (22)f

    = - 35v + 22f